2011
DOI: 10.1007/s11948-011-9319-6
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Sensitivity to Conflicts of Interest: A Preliminary Test of Method

Abstract: This study presents and develops test methods for assessing sensitivity to conflict of interest (COIsen). We are aware of no study assessing COIsen, but note that some popular methods for assessing ethical sensitivity and related constructs (which include COIsen) are flawed in that their presentation of stimulus material to subjects actually guides subjects to attend to ethical (or related) issues. The method tested here was designed to avoid this flaw. Using adaptations of two existing cases, a quota sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Lind and Swenson-Lepper focused on measuring students' ability to recognize conflicts of interest (COIs) but did not extend to other examples of ethical dilemmas. Even so, their study found COI scores to vary greatly amongst participants [50].…”
Section: Ethical Sensitivity Assessment In Engineeringmentioning
confidence: 93%
“…Lind and Swenson-Lepper focused on measuring students' ability to recognize conflicts of interest (COIs) but did not extend to other examples of ethical dilemmas. Even so, their study found COI scores to vary greatly amongst participants [50].…”
Section: Ethical Sensitivity Assessment In Engineeringmentioning
confidence: 93%
“…Previous research on professional ethics was conducted either by qualitative content analysis of codes of ethics from professional bodies or by quantitative surveys to study individuals' ethical skills or sensitivity (e.g., Casali, 2011; Lind & Swenson‐Lepper, 2013; Shawver & Sennetti, 2009). Both approaches have their limitations.…”
Section: Empirical Backgroundmentioning
confidence: 99%
“…Additionally, in NHV we have striven to move beyond the abstract presentation of professional codes to discussing concrete stories and current events in order to increase ethical sensitivity (Jagger 2011;Lind & Swenson-Lepper 2013) and cultivate moral imagination and moral judgement (Pardales 2002). Holsapple, et al (2012) show that students perceive codes as merely rules and laws that lack complexity and real-world application.…”
Section: Curricular Development and Implementationmentioning
confidence: 99%